2016
DOI: 10.4028/www.scientific.net/amm.851.803
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on GFRP Reinforced Concrete Mixed with Sea Sand and Sea Water

Abstract: The development of marine economy brings with it a need for marine buildings and port structures that require concrete. If these buildings were built with sea sand concrete mixed with sea water instead of traditional concrete and replaced FRP reinforced steel, raw materials can be procured locally, saving time and cost. Based on the above considerations, 8 GFRP reinforced SS-concrete (concrete with sea sand and sea water) beams were prepared to understand their workability and strength as their reinforcement r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…(3) Slumps Slump is a special measurement of concrete and workability method and indicators to measure its degree, to judge whether the construction can be carried out normally. Although the slump of seawater marine aggregate concrete is slightly smaller than that of freshwater concrete, overall, Xing Li [8] and Chen [9] show that the slump of seawater sand concrete increases and decreases respectively with the increase of chlorine salt and shell content. When Younis et al [10] study found that the water glue ratio was the same, Compared with freshwater concrete, the slump of seawater concrete is reduced by 20%.…”
Section: Working Performance Of Seawater and Marinementioning
confidence: 99%
“…(3) Slumps Slump is a special measurement of concrete and workability method and indicators to measure its degree, to judge whether the construction can be carried out normally. Although the slump of seawater marine aggregate concrete is slightly smaller than that of freshwater concrete, overall, Xing Li [8] and Chen [9] show that the slump of seawater sand concrete increases and decreases respectively with the increase of chlorine salt and shell content. When Younis et al [10] study found that the water glue ratio was the same, Compared with freshwater concrete, the slump of seawater concrete is reduced by 20%.…”
Section: Working Performance Of Seawater and Marinementioning
confidence: 99%